Can we trust self-reported walking distance when determining EDSS scores in patients with multiple sclerosis? The Danish MS hospitals rehabilitation study. (October 2019) - Skjerbæk, Anders Guldhammer; Boesen, Finn; Petersen, Thor; Rasmussen, Peter Vestergaard; Stenager, Egon; Nørgaard, Michael; Feys, Peter; Kjeldgaard-Jørgensen, Marie Louise; Hvid, Lars Grøndahl; Dalgas, Ulrik
Background: In multiple sclerosis (MS), the Expanded Disability Status Scale (EDSS) reflects disease severity. Although parts of the EDSS are dependent on actual walking distance, self-reported statements are often applied. Objectives: The purpose of the present study was, therefore, to compare self-reported walking distance to actual walking distance to outline how this influences EDSS scoring. Methods: MS patients with EDSS 4.0–7.5 ( n  = 273) were included from the Danish MS hospitals rehabilitation study ( n  = 427). All patients subjectively classified their maximal walking distance according to one of seven categories (>500; 300–499; 200–299; 100–199; 20–99; 5–19; 0–4 m). Subsequently, actual maximal walking distance was assessed and EDSS was determined from both self-reported walking distance (EDSSself-report ) and actual walking distance (EDSSactual ). Results: In 145 patients (53%), self-reported walking distance was misclassified when compared to the actual walking distance. Misclassification was more frequent in patients using walking aids (64% vs. 44%, p  < 0.05) and in patients with primary progressive MS (69%, p  < 0.05). Misclassification of walking distance corresponded to incorrect EDSS scores (EDSSself-report vs EDSSactual ) of ⩾0.5 point in 24%. Conclusion: In MS patients with EDSS 4.0–7.5, 53% misclassified their walking distance yielding incorrect EDSS scores in 24%. Therefore, correct EDSS determination must be based on measurement of actual walking distance.